Analysis of maximization strategy intangible assets through the speed of innovation on knowledge-driven business performance improvement - I Gusti Ayu Purnamawati; Ferry Jie; Chin-Hong Puah; Gede Adi Yuniarta (Economies, 2022)
This study aims to determine the effect of human capital, structural capital, and consumer capital on financial performance and moderate the speed of innovation. The type of research used in the study is quantitative-data collection techniques in distributing questionnaires measured using a Likert scale. The sampling technique used was random sampling and was determined by the slovin formula. The population in this study was MSMEs in Buleleng Regency, and the samples used in this study amounted to 392 MSMEs. Data or statistical analysis techniques in the study were considered using the Structural Equation Model with WarpPLS 5.0 software modelling. The results show that the technology and commitment variables have no significant effect on the development of religious ecotourism villages. In contrast, cultural changes significantly impact the development of religious ecotourism villages. This study uses the speed of innovation as a moderating variable, the speed of innovation is one of the essential things for MSMEs to improve financial performance. The speed of innovation supports intellectual capital, which is currently focused on knowledge-driven business to create a competitive advantage.
Keywords: 330; financial performance; intellectual capital; thespeed of innovation